Rechterlijk Pardon Concept for Elderly Criminal Offenders: Konsep Rechterlijk Pardon Bagi Pelaku Tindak Pidana Lansia - Angga, Angga; Maskur, Muhammad Azil (Annual Review of Legal Studies, 2024)
The concept of rechterlijk pardon is a reform in the Criminal Code that can ease the burden on elderly people who are perpetrators of criminal acts. Efforts to avoid being sentenced to prison remind the author of restorative justice which prioritizes restoration or returning to the original situation for both the victim and the perpetrator. In this research, there are 2 (two) problem formulations, namely whether the rechterlijk pardon concept can be applied to elderly criminal offenders and how the rechterlijk pardon concept can be applied to elderly criminal offenders to realize restorative justice. This research uses a qualitative research approach and normative juridical research. The research focuses on juridical review in the concept of rechterlijk pardon in the Criminal Code. Research comes from primary legal materials such as the Criminal Code and relevant legal instruments, then secondary legal materials, such as books and literature in the form of legal journals, and various dictionaries as tertiary legal materials. Triangulation techniques are used to validate data with sources, theories and previous research. Based on this research, according to the concept of rechterlijk pardon in the Criminal Code, judge forgiveness can be applied to criminal offenders aged 75 years and over. However, based on research regarding the physical and psychological condition of the elderly, elderly people under 75 years also require special attention in sentencing. Apart from that, the concept of rechterlijk pardon would be better if it worked in accordance with restorative justice which provides a win-win solution for both the victim and the perpetrator.